Gisèle Pelicot settles claim for invasion of privacy against French magazine - Chrisafis, Angelique (The Guardian, 2025)
Pelicot, who became a feminist hero after she decided to waive her right to anonymity in the trial of her former husband and 50 other men last year, took legal action against the publication in April.
Keywords: Europe; France; Gisèle Pelicot; Gisèle Pelicot rape trial; Media; Privacy & the media; World news